Kinerja Dinas Lingkungan Hidup Bidang Kebersihan Dalam Penanganan Sampah di Kota Gorontalo - Ngabito, Sutanti Putri; Sulila, Ismet; Aneta, Yanti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aims to determine the performance of the Environmental Service in the Cleanliness Sector in Handling Waste in Gorontalo City as seen from the dimensions of (1) Productivity, (2) Responsiveness, (3) Responsibility, and (4) Accountability. The research method used is qualitative with descriptive research type. Data collection was carried out by observation, interviews and documentation. The results of this research show that the performance of the Environmental Service in the field of cleanliness in handling waste in Gorontalo City has been carried out well, but in terms of (1) Productivity has not reached the target in JAKSTRADA due to limited workforce, facilities and infrastructure, and budget. (2) Responsiveness is still lacking because there are still complaints from the public about untreated waste and from cleaning staff. (3) Responsibility for the implementation of TUPOKSI is still lacking because it has not been supported by training that is appropriate to the responsibilities held, as well as public awareness regarding waste handling. (4) Accountability is still lacking because there is a mismatch between the duties and positions held.